(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The objective of this study was to evaluate the effect of the isolated and joint use of Azospirillum brasilense inoculation and the application of thiamine, on seed or leaf, on the development of millet in two cycles. A randomized complete block design was used in five replicates. The treatments were composed of the isolated or combined inoculation with Azospirillum brasilense and the application of thiamine, on seed (10 ml kg-1) or leaf spray (10 ppm). The relative levels of chlorophyll a, b and total, plant height, number of shoots, fresh and dry mass production and dry matter index of plants were evaluated. In the first cycle, treatments were only effective for the relative chlorophyll contents, and in general, the treatment with isolated inoculation of A. brasilense stood out, differing significantly from the treatment with thiamin applied on seed. In the second cycle, there was significant effect of the treatments on the variables of plant height and number of shoots, in which a maximum height of 165 cm and production of 140 shoots m-2 with application of thiamin on seed and with the use of A. brasilense and thiamine applied on the leaf, respectively. Thus, it was concluded that inoculation with A. brasilense increases the relative chlorophyll content in millet during the first cycle. The joint use of inoculation with A. brasilense and the application of thiamine can be used as a strategy to increase the number of shoots.